Estudio del contenido informativo de la sección Comunidad de diario Crónica en su versión digital publicada en Facebook y el impacto en sus lectores. Período: abril – junio 2023 - Encarnación Ordóñez, Jordy Osmanie (2024)
This research work is directed and focused on the study of the informative content of the Community section of Crónica newspaper in its digital version and the impact on its readers in the period April - June 2023, with the purpose of analyzing the community content issued in its issues and distributed in the social network Facebook. The study includes a literature review where the theoretical contributions developed by various authors are presented to support the study. It also reflects the data collected through surveys, which allowed supporting the research. Among the objectives of the research are to identify the sections and news genres of Crónica newspaper and also to establish the degree of interest and interaction that the newspaper generates among its readers. Likewise, a methodology with a mixed approach was implemented, qualitative-quantitative methods were combined, therefore, techniques such as interviews, observation sheets, content analysis and surveys were taken into account. The results show that the journalistic products inserted in the Community section of the Crónica newspaper present an adequate informative structure, with community events as their main focus. In addition, the section generates great interest and interaction in its readers, since the topics covered are linked to various community sectors. However, it was noted that the section has little space in the newspaper. Finally, the informative contents of the Community section of Crónica newspaper in its digital version contain a good informative structure, since they comply with the basic elements and parameters on news events for the dissemination of community contents. Keywords: Community contents; Digital newspaper; Community; Facebook; Crónica newspaper.